Hunting Prince Dracula - Maniscalco, Kerri (Maniscalco, Kerri. Stalking Jack the Ripper, 2018)
"Bizarre murders are discovered in the castle of Prince Vlad the Impaler, otherwise known as Dracula. Could it be a copycat killer...or has the depraved prince been brought back to life?"-- Provided by publisher